PROFIL FITOKIMIA MENGGUNAKAN GC-MS DAN POTENSI ANTIOKSIDAN SPESIFIK GEOGRAFIS: STUDI KOMPARATIF Vernonia cinerea L. ETNIS NIAS GUNUNG SITOLI - Sari, Mayang; Ginting, Mandike; Damayanti, Rizki; Zega, Nufdar (UIN AR-RANIRY, 2026)
Vernonia cinerea L. (VCL) leaves have been known in several countries to have various medical activities as a fever reducer, diuretic, antispasmodic and anthelmintic, relieve asthma, cough, malaria, urinary tract stones and arthritis. In Indonesia, this type of plant can also be found as a wild plant. This study investigated the determination of active compounds from ethanol extract of leaves using GC-MS and determination of antioxidant activity of various extracts Antioxidant activity of the DPPH method. Analysis with FTIR obtained several peaks representing the identity of the compounds in the extract is at a wavelength of 3351.95 cm-1 determination of alcohol and amine groups (O-H., N-H), 2924,62 cm-1 is in the C-H bond., -CH3., C=C-H., Ar-H, 1616,25 cm-1 is in the carboxyl group (COOH), amine and amide groups at 1600-1650 cm-1. And at a wavelength of 1030-1068,45 cm-1 which is a primary alcohol group (CH2OH). Analysis with GC-MS obtained promising bioactive compounds in the health sector, there are 11 main components, namely: hexadecanoic acid methyl ester., n-hexadecanoic acid., 9,12,15-octadecatrienoic acid, methyl ester, (Z,Z,Z)., Neoptadine., hydroxymethylfurfurole., Dodecanamide., 9-Octadecenamide, dodecanamide, N,N-bis (2-hydroxyethyl)., vinyl phenol., vomifoliol., 13-OXABICYCLO [10.1.0] TRIDECANE. And the results of the antioxidant activity test showed that the VCL ethanol extract has strong antioxidant activity with an IC50 value of 64,907±0,02 (mg/L) which has the potential as a natural antioxidant.